Exploring neutrino masses and mixing in the seesaw model with $L_e-L_τ$ gauged symmetry - Panda, Papia; Kumar Behera, Mitesh; Mishra, Priya; SINGIRALA, SHIVARAMAKRISHNA; Mohanta, Rukmani (SciPost physics proceedings, 2025)
We investigate neutrino phenomenology in the U(1)_{L_e-L_τ} U ( 1 ) L e − L τ gauge extension of the Standard Model with symmetry following the framework of type-(I+II) seesaw mechanism. For this, we have added three right handed neutrinos, one singlet and one scalar triplet in our model. We show that the model can successfully accommodate the observed neutrino oscillation data and consistent with the results from lepton flavor violation and neutrinoless double beta decay process.